Chinese Strategy Of «One Belt And One Way» - DIKAREV, O.I.; SHOSTAK, L.B. (Zenodo, 2018)
The subject of the study is the Belt may offer limited prospects as a platform for broader EU China cooperation on harder security issues in Eurasia. However, it does represent an opportunity for the EU to work towards closer development–security cooperation on a range of softer security or developmental topics. The purpose of the article.– The referral to the BRI’s topic is justified by search of qualified ground from which to answer some of questions: (1) is any measure of interaction and dependence of traditional context China’s stratagems’ geopolitics and modern international relation principal: (2) about dreams of China elite not only about expanding the Chinese economy by acquiring resources and markets for China’s exports, but also on modernizing the world’s largest military force; (3) about possibility of a more aggressive Chinese foreign policy behaviour with declarations of more air defence identification zones and introductions of more oil drilling rigs and artificial islands in disputed territorial waters; (4) to advance its own diplomatic concepts and initiatives such as the Asian Infrastructure Investment Bank (AIIB) and the BRICS–bank and thereby more proactively seek to shape the international system; (5) the ports, railroads of the OBOR could be used to transport China’s military forces across Asia in the future in order to push pendulum of world economy to swung from West to East. Methodology of the work – For the above analysis were used wide range of sources and made different comparison but it is still very preliminary but it does support a gradual development of new thinking and a new approach in China’s OBOR’s foreign policy strategy under Xi that point to big changes in the way that China engages with the international system. Further research is needed and it seems especially important to focus on the implications of the domestic focus in the Chinese leadership – that is their focus on meeting the growing domestic expectations to the role that China will play in the international system in the years to come. But already possible to say that so a kind stratagem’s «crossing the river by feeling for the stones» approach still seems to best characterize the overall development in Chinese foreign policy behaviour rather than a new overall guiding strategy or master plan of OBOR. The results of the work – It has been established that the Chinese elite is updating: (1) its own concept of infrastructure development in the adversarial triad of the options «(1) USA– (2) EU– (3)»; (2) the elite of Central Asian countries, in particular, the Chinese leaders took advantage of the relative decline of influence Russia and the United States in Afghanistan to expand its influence; (3) The Chinese concept of the new Silk Road is aimed at ensuring the supply of natural resources, in particular energy resources – land from gas and oil deposits in Central Asia, and through the sea through the Malacca Strait and the Arctic regions. Conclusions – A part of what have been signified «new OBOR» are in fact previously carried over projects which are being given new life became a part of «China dream». Hu Jintao had earlier said about new Silk Road initiative, but it had not gone anywhere. This stratagem was the first to call on Chinese enterprises and industries to «go out» and invest abroad. That is why OBOR is «upgrade» of China’s Going Out policy for China’s businesses and industries. The stratagem of the China Dream was directed to implementing balance between collective identity and individual aspirations: Chinese people feel as having a collective will and identity shaped by a difficult history. It claims that Xi as the first Chinese leader since Deng is strong enough to push through a rethinking of China’s foreign policy strategy. The Belt is a long–term Chinese connectivity vision with no a priori parameters on methods, actors or mechanisms, nor much granularity to date. It therefore allows a great deal of flexibility and could become a leading new model of cooperation and global governance. The Belt will certainly expand China’s overseas security interests and will require China to take an increasingly active stance on regional security affairs, not least to protect its investments. China’s non–interference stance, which has already been evolving over the past few years, will likely become much more creative in the future. Yet, how this unfolds will depend on the specific security dynamics in Belt target states, as the Belt resources interest implementation progresses.